Penerapan Gender Analysis Pathway dalam Mengatasi Pernikahan Usia Dini di Desa Margopatut Kabupaten Nganjuk - Ratna Frenty Nurkhalim; Mia Ashari Kurniasari (GUYUB: Journal of Community Engagement, 2024)
Early-age marriages are still a serious problem in Indonesia, especially in rural areas.  In this activity we analyzed the phenomenon of early marriage in the village of Margopatut, Nganjuk district, by applying the Gender Analysis Pathway (GAP). The aim is to identify the causes of early marriage, develop a gender-responsive intervention program for the village. Through the analysis of GAP, it has been found that early marriages are still dominated by women, with some factors including poor understanding of the maturity of marriage age and family economic conditions. Recommended intervention programmes include counseling, training, selection of gender ambassadors, and advocacy for strengthening education and career training for women. We concluded that tackling early-age marriages requires a gender-responsive and sustainable approach as well as cooperation between governments, communities, and relevant institutions. This GAP analysis can be a basis for developing policies and programmes that are more effective in dealing with early-age marriages, and can be put forward in the village distribution activities